Experiencing Visible and Invisible Metal Casting Techniques in Bronze Age Italy - Monia Barbieri (EXARC, 2015)
What we know about Bronze Age metalworking in Italy basically relies on finished artefacts and on stone, clay or bronze implements involved in the process of manufacturing (tuyères, crucibles, moulds, hammers, chisels, et cetera; Bianchi, 2010; Bianchi, in press). Moreover, evidences of structures for casting are extremely poor, at least in Italy, likely because of a lack of extensive excavations and, in absence of metalworking residuals, the difficulty to clearly distinguish them from other kinds of firing structures (Cavazzuti et al. in press). The reconstruction of the whole technology of production therefore requires a strong effort of making and testing hypotheses, referring not only to autoptic observations on archaeological finds, but also to archaeometrical analysis and study of landscape, in order to identify possible sources of raw materials. In this work our aim is to deepen some aspects concerning archaeologically ‘visible’ (stone mould production and casting), and ‘invisible’ techniques (sword production) of metalworking in Bronze Age Italy, focussing on Terramare context.